You would substitute or plug in -5 wherever there is an x in the equation.
f(-5) = 6(-5) + 7
f(-5)= -30 + 7
f(-5) = -23
Answer:
should be 43
Step-by-step explanation:
because it goes up by 2 every time
Answer:
500.
Step-by-step explanation:
(1 * 10^6) / (2 * 10^3)
= 1/2 * 10^6/10^3
= 0.5 * 10^3
= 5 * 10^2
= 500.
6 eggs (i think)
5x12=60 cookies require 2 eggs
30x12=360
360 divided by 60= 6
so six eggs
The answer is C,
as she uses SSS to prove its congruent, she uses sides instead of angles so option a and d is not correct. as it needs to prove triangle pqr is congruent to triangle sqr, its not necessary to prove PQ is equal to QR. so the answer is c